2017
DOI: 10.1038/s41598-017-11304-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in the Splenic Transcriptome of Chickens during the Early Infection and Progress of Marek’s Disease

Abstract: Gallid alphaherpesvirus 2 (GaHV2) is an oncogenic avian herpesvirus inducing Marek’s disease (MD) and rapid-onset T-cell lymphomas. To reveal molecular events in MD pathogenesis and tumorigenesis, the dynamic splenic transcriptome of GaHV2-infected chickens during early infection and pathogenic phases has been determined utilizing RNA-seq. Based on the significant differentially expressed genes (DEGs), analysis of gene ontology, KEGG pathway and protein-protein interaction network has demonstrated that the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…MDV infects and causes alterations in proliferation and activation of B cells. Studies have shown that MDV affects the disease outcome by merely altering or controlling the host cellular machinery in order to facilitate its replication [40]. Meanwhile, it is the innate immune response that is chiefly involved in the battle against invading MDV.…”
Section: Discussionmentioning
confidence: 99%
“…MDV infects and causes alterations in proliferation and activation of B cells. Studies have shown that MDV affects the disease outcome by merely altering or controlling the host cellular machinery in order to facilitate its replication [40]. Meanwhile, it is the innate immune response that is chiefly involved in the battle against invading MDV.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of ChERVs in ALV-J, AIV, MDV and APEC infected samples and corresponding uninfected samples. RNA-seq data from ALV-J (A) [23], AIV (C) [24], MDV (E) [25] and APECinfected chicken (F) [26] and corresponding uninfected controls were aligned using TopHat and transcripts were constructed using Cufflinks. The number of fragments per kilobase per Expression of ChERVs in ALV-J, AIV, MDV and APEC infected samples and corresponding uninfected samples.…”
Section: Discussionmentioning
confidence: 99%
“…The published splenic transcriptome raw data of MDV-infected samples and uninfected samples at 14 dpi were selected for ChERVs transcriptome analysis [25]. Two cDNA libraries of MDV-infected and uninfected samples were designated as CH-14dpi (SRA:SRX2425016) and CH-14d (SRA:SRX2425017).…”
Section: Four Transcriptome Raw Data Of Chicken Pathogenic Microorganismmentioning
confidence: 99%
See 2 more Smart Citations